تطوير وسيلة التعليم المبنية على البطاقات المصورة على مادة “البيت” لطلبة الصف السابع بالمدرسة الثانوية داتوك سليمان للبنين فالوفو: The Development of Picture Card-Based Teaching Media for the Lesson “Al-Bayt” (The House) among Seventh-Grade Students at Datok Sulaiman Boys’ Secondary School - Nini Angriani; Mardi Takwim; Aishiyah Saputri Laswi (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
This research aims to determine the development process, the validity level of the product, the practicality of the product, and the effectiveness of the developed product. This type of research is research and development (R&D), adapting the 4D development model, which consists of four stages: define, design, development, and disseminate. The subjects of this research were the seventh-grade students of Madrasah Tsanawiyah Datuk Sulaiman Palopo. Data collection techniques used were observation, interviews, validation sheets, student response questionnaires, documentation, and tests. Data were analyzed using quantitative data analysis techniques. The results of this development research showed that the comic learning media had passed the validation stages by experts with the following results: (1) validation from media experts obtained a score of 95%; (2) validation from subject matter experts obtained a score of 98.33%; (3) validation from practitioner experts reached a score of 95%, and the practicality trial resulted in an average score of 87.67%; (4) product feasibility/effectiveness test resulted in an average score of 86.56%. Based on the validation results from the three expert validators and the practicality test results, it can be concluded that the use of picture cards as a learning medium is feasible, fulfilling the criteria of being valid, practical, and effective, and thus can be applied in Arabic language learning. يهدف هذا البحث إلى معرفة عملية التطوير ومستوى صلاحية المنتج ومستوى التطبيق العملي للمنتج ومستوى فعالية المنتج المطور. هذا النوع من البحث هو البحث والتطوير (R&D) من خلال تكييف نموذج التطوير رباعي الأبعاد الذي يتكون من أربع مراحل ، وهي التعريف والتصميم والتطوير والنشر. موضوع هذه الدراسة هو طالب الصف السابع في مدرسة تساناوية داتوك سليمان فالوفو. تستخدم تقنيات جمع البيانات الملاحظة والمقابلات وأوراق التحقق واستبيانات رد الطلاب والتوثيق والاختبارات. تم تحليل البيانات باستخدام تقنيات تحليل البيانات الكمية. تظهر نتائج هذه الدراسة التنموية أن وسيلة التعلم الهزلي قد مرت بمرحلة التحقق من الصحة من قبل الخبراء بالنتائج التالية: (1) تم التحقق من صحة خبراء التعليم للحصول على درجة 95٪. (2) حصل التحقق من صحة خبراء المادة على درجة 98.33٪ ؛ (3) وصلت الدقة من الممارسين الخبراء إلى 95٪ ، وحصلت نتائج اختبار التطبيق العملي على متوسط نسبة مئوية 87.67٪ ؛ (4) اختبار جدوى / فعالية المنتج بمتوسط درجة 86.56٪. بناء على نتائج التحقق من صحة المدققين الخبراء الثلاثة ونتائج اختبارات التطبيق العملي ، يمكن استنتاج أن استخدام البطاقات المصورة كوسيلة تعليمية ممكن مع استيفاء معايير صحيحة وعملية وفعالة بحيث يمكن تطبيقها في تعلم اللغة العربية.